Telehealth Home Monitoring and Postcardiac Surgery for Congenital Heart Disease - Medoff Cooper, Barbara (Pediatrics, 2020)
OBJECTIVES: To test the effect of a 4-month telehealth home monitoring program (REACH), layered on usual care, on postdischarge outcomes in parents of infants recovering from cardiac surgery and their infants. METHODS: Randomized trial of infants discharged from the hospital after cardiac surgery for congenital heart disease. Consecutive infants with complex congenital heart disease undergoing cardiac surgery within 21 days of life were enrolled at 3 university-affiliated pediatric cardiac centers. RESULTS: From 2012 to 2016, 219 parent-infant dyads were enrolled; 109 were randomly assigned to the intervention group and 110 to the control group. At 4 months postdischarge, parenting stress was not significantly different between groups (total Parenting Stress Index in the intervention group was 220 and in the control group was 215; P = .61). The percentages of parents who met posttraumatic stress disorder (PTSD) criteria and parent quality of life inventory scores were also not significantly different between the 2 groups (PTSD in the intervention group was 18% and was 18% in the control group; P =.56; the mean Ulm Quality of Life Inventory for Parents in the intervention group was 71 andwas 70 in the control group; P = .88). Infant growth in both groups was suboptimal (the mean weight-for-age z scores were −1.1 in the intervention group and −1.2 in the control group; P = .56), and more infants in the intervention group were readmitted to the hospital (66% in the intervention group versus 57% in the control group; P < .001). CONCLUSIONS: When added to usual care, the REACH intervention was not associated with an improvement in parent or infant outcomes. Four months after neonatal heart surgery, ∼20% of parents demonstrate PTSD symptoms. Suboptimal infant growth and hospital readmissions were common.